2019
DOI: 10.1103/physreva.99.013435
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high-order harmonic generation in donor-doped band-gap materials

Abstract: We find that a donor-doped band-gap material can enhance the overall high-order harmonic generation (HHG) efficiency by several orders of magnitude, compared with undoped and acceptordoped materials. This significant enhancement, predicted by time-dependent density functional theory simulations, originates from the highest occupied impurity state which has an isolated energy located within the band gap. The impurity-state HHG is rationalized by a three-step model, taking into account that the impurity-state el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
58
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 47 publications
5
58
2
Order By: Relevance
“…[16] for a modern introduction into the topological aspects of the SSH model). Figure 1 illustrates the connection between the modelling using the very simple SSH tight-binding approach (leading to two bands only) [16,41,42,44] and the abinitio density-functional theory (DFT) on a fine-grained position-space grid [28,31,[45][46][47]. Let us first consider the upper panel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] for a modern introduction into the topological aspects of the SSH model). Figure 1 illustrates the connection between the modelling using the very simple SSH tight-binding approach (leading to two bands only) [16,41,42,44] and the abinitio density-functional theory (DFT) on a fine-grained position-space grid [28,31,[45][46][47]. Let us first consider the upper panel.…”
Section: Introductionmentioning
confidence: 99%
“…The atoms are shifted from their equidistant positions (lattice constant a) alternatingly by δ to the right and left, generating the two possible dimerizations called phase A and phase B. For the case of one electron per ion, the equidistant configuration is metallic (half populated lowest band) but energetically less favor- Connection between atom positions on a finegrained, real-space grid as used in DFT [28,31,[45][46][47] and the SSH model [16,41,42] to illustrate the discussion in the Introduction.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen the emergence of highharmonic generation (HHG) in solids [1][2][3][4][5][6] as a promising and compact ultrafast light source, as well as a potential tool to reconstruct crystal band structures [7], measure Berry curvatures [8,9], and probe topological phase transitions [10][11][12]. Complementing experimental progress, a number of theoretical studies have explored HHG in solids either in terms of reciprocal-space dynamics within the band structure [1,5,6,[13][14][15][16][17][18][19][20][21][22][23], which contains both intra-and interband contributions, or in terms of realspace particle-like dynamics in the crystal [2,3,14,[24][25][26][27][28][29].…”
mentioning
confidence: 99%
“…We found that the spatial width of the electron and hole wave packets can be almost one order of magnitude larger than the lattice constant, allowing for the imperfect recollisions. This suggests that the harmonic emission can probe the degree of spatial homogeneity of the periodic structure [25,39,[53][54][55] as well as the temporal dephasing introduced by e.g. electron correlation.…”
mentioning
confidence: 99%
“…By introducing dopants, we can alter the electronic structure and change the non-linear optical properties of the crystal. This could be used to tailor certain materials for strong field optoelectronics applications, for example a new degree of control in solid-state high harmonics [17].…”
Section: Introductionmentioning
confidence: 99%